PTU-112 Presentation, treatment and clinical outcome of collagenous and lymphocytic colitis over a 6-year period in a single UK centre. (28th May 2012) - Naghibi, M; Akbar, T; Gordon, J N
Abstract : Introduction: Collagenous colitis (CC) and lymphocytic colitis (LC) are referred to collectively as microscopic colitis (MC). CC and LC represent an increasingly common cause of chronic diarrhoea. However, clinical and epidemiological data on these diseases are scare and diagnosis is often delayed. Optimal treatment, especially of resistant cases, remains to be defined. We therefore aimed to investigate the incidence, presentation, treatment and outcome of patients from a single UK centre. Methods: Clinical data were retrospectively collected from electronic and paper records for all patients diagnosed with CC and LC at this institution from April 2004 to November 2011. Results: 104 patients were identified of which 68 (65%) had CC and 36 (35%) LC. The median age at diagnosis for MC was 70 years (range 36–90 years), with 18% being under the age of 55 years. The overall MC female to male sex ratio was 2.8:1. The incidence of MC rose tenfold during the study from 0.67 to 6.67 per 100 000 population/year. Presentation was similar between CC and LC with diarrhoea present in all cases and nocturnal diarrhoea in 41%, abdominal pain in 36%, weight loss in 34% and nausea in 12%. 58 (56%) were referred through the surgical pathway, often via 2-week-wait pathway. Diagnosis could be made from left sided biopsies in 96/102 (94%). The median number of days between histological diagnosis and commencement of treatment was 54 days with no significant difference between medical and surgical referral pathways. 46 (48%) patients were treated with budesonide with an immediate response in 42 (92%), though 54% of responders subsequently relapsed. The vast majority of budesonide sensitive patients responded to a further course of budesonide with continuing disease activity rare after a third treatment course. Budesonide was more likely to be started as first line treatment in the medical pathway compare to surgical. Of all cases, drug withdrawal was part of the treatment in 12 cases resulting in complete clinical remission in eight patients with a further two patients reporting a modest improvement. Six (6%) patients required long-term maintenance therapy, four with budesonide and two with azathioprine. Conclusion: The incidence of both CC and LC increased over the period of the study in keeping with other European studies. A significant proportion of patients presented below the age of 55. Lansoprazole and NSAID use are both more common in CC than LC. Left-sided biopsies were sufficient for diagnosis in the vast majority of cases. Budesonide therapy is an effective strategy but long term maintenance therapy requires further investigation. Competing interests: None declared.